Sex differences and hormonal effects on gut microbiota composition in mice. (3rd July 2016) - Org, Elin; Mehrabian, Margarete; Parks, Brian W.; Shipkova, Petia; Liu, Xiaoqin; Drake, Thomas A.; Lusis, Aldons J.
ABSTRACT: We previously reported quantitation of gut microbiota in a panel of 89 different inbred strains of mice, and we now examine the question of sex differences in microbiota composition. When the total population of 689 mice was examined together, several taxa exhibited significant differences in abundance between sexes but a larger number of differences were observed at the single strain level, suggesting that sex differences can be obscured by host genetics and environmental factors. We also examined a subset of mice on chow and high fat diets and observed sex-by-diet interactions. We further investigated the sex differences using gonadectomized and hormone treated mice from 3 different inbred strains. Principal coordinate analysis with unweighted UniFrac distances revealed very clear effects of gonadectomy and hormone replacement on microbiota composition in all 3 strains. Moreover, bile acid analyses showed gender-specific differences as well as effects of gonodectomy, providing one possible mechanism mediating sex differences in microbiota composition.